Conservation agriculture has no significant impact on sheep digestive parasitism - ElHamdi, Sihem; Sassi, Limam; Rekik, Mourad; Dhehibi, Mokhtar; Cheikh M'hamed, Hatem; Gharbi, Mohamed (Frontiers in Veterinary Science, 2023)
Conservation agriculture (CONS A) is a sustainable agriculture system which is based on crop rotation crops with no tillage. It has various environmental advantages compared to conventional agriculture (CONV A), namely decrease water evaporation, erosion and CO2 emission. We report herein the first study aiming to evaluate the impact of this type of agriculture on sheep gastrointestinal parasites. Two lamb groups aged between six five and ten months were randomly included to graze separately on CONS A and CONV A pastures. Each group was constituted of two batches of three lambs that were followed up for two rearing months. Liveweight, haematological parameters variation and digestive parasites were studied. At the end of the study period, lambs were slaughtered then the carcass yield was determined and a helminthological autopsy was performed on the digestive tracts of animals to estimate different parasitological indicators.There was no difference between lambs rearing on CONS A and those rearing on CONV A for all parasite indicators (infestation intensity, abundance and prevalence), the same trend was also obtained for haematological parameters, liveweight evolution and carcass yield. These results prove that there is no impact of the CONS A on the sheep digestive parasitism. Further studies are needed to support these findings on a larger animal samples and to investigate the impact of the conservation agriculture on other parasite species. Similar studies could be also implemented on other ruminant species.